The Role of Microfinance in Asset-Building and Poverty Reduction : The Case of Sinapi Aba Trust of Ghana /: The Case of Sinapi Aba Trust of Ghana. (March 2009) - Adjei, Joseph Kimos; Arun, Thankom; Hossain, Farhad
No abstract available